1997
DOI: 10.1017/s003118209700173x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ras, MAP kinases, and a GAP protein in Schistosoma mansoni by immunoblotting and their putative involvement in male–female interaction

Abstract: The maturation of female Schistosoma mansoni depends on pairing with a male which induces mitotic activities in the reproductive organs of the female worm. Since in other organisms cell proliferation is regulated by well-conserved signal transducing molecules, we looked for such molecules on immunoblots of schistosomes, using antibodies against conserved epitopes of Ras, GAP and MAP kinases. We identified all 3 molecules in schistosomes and found that they are developmentally regulated. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…Orthologs of EGFR and IR [28][29][30] (described below) as well as components of the Ras/MAP kinase pathway have been characterized in the trematode S. mansoni and in the cestode E. multilocularis. Biochemical evidence has been provided that Ras, MAP kinase and the Ras-interacting GAP proteins are developmentally regulated in S. mansoni and possibly involved in male-directed maturation of female parasites [31]. The S. mansoni Ras protein (SmRas) was then shown to be similar to K-Ras from diverse species [32,33].…”
Section: Rtk and Ras/map Kinase Signalling Pathways In Parasitesmentioning
confidence: 99%
“…Orthologs of EGFR and IR [28][29][30] (described below) as well as components of the Ras/MAP kinase pathway have been characterized in the trematode S. mansoni and in the cestode E. multilocularis. Biochemical evidence has been provided that Ras, MAP kinase and the Ras-interacting GAP proteins are developmentally regulated in S. mansoni and possibly involved in male-directed maturation of female parasites [31]. The S. mansoni Ras protein (SmRas) was then shown to be similar to K-Ras from diverse species [32,33].…”
Section: Rtk and Ras/map Kinase Signalling Pathways In Parasitesmentioning
confidence: 99%
“…It is now clear that the ability of S. mansoni to survive for decades in the blood-stream of its host and the sexual maturation of the female that depends on a close contact with the male are processes that require molecular communication (Schussler et al 1997, Kunz 2001, Kapp et al 2004.…”
Section: S Mansoni Proteins Involved In Signal Transductionmentioning
confidence: 99%
“…Molecular studies have finally demonstrated that the male even governs the transcriptional activity of female-specific genes expressed in the reproductive organs, such as those encoding eggshell precursor proteins [25]. During this early time of molecular research on male-female interaction first evidence was obtained that signal transduction cascades could be involved in the control of such processes [26].…”
Section: Introductionmentioning
confidence: 99%